Bird species distribution and conservation in Serra do Cipo, Minas Gerais, Brazil - Melo, T. A.; De Vasconcelos, M. F.; Fernandes, G. W.; Marini, M. A. (Cambridge University Press, 2001)
We studied the distribution of birds along an altitudinal gradient ranging from 800 m to 1,400 m on two slopes of the Serra do Cip6, Minas Gerais, southeastern Brazil. Ornithological surveys were conducted over transects covering open (cerrado, campo rupestre) and forested (gallery and Atlantic forest) habitats from 1994 to 2000. We found 273 bird species belonging to 51 families. Twenty-two species were restricted to higher elevations and 84 Species were detected on only one slope, depending on the vegetation type they inhabited. We recorded 104 species occurring on both slopes, while 61 species were considered altitudinal generalists. Six species, including Hyacinth Visorbearer Augastes scutatus and Cip6 Canastero Asthenes luizae were restricted to the highest parts of Serra do Cip6, a fragile habitat important to endemic birds of the Espinhaco Range. In the past 10 years, the Serra do Cip6 region has suffered human impacts on a large scale, and conservation action must be developed to protect the fauna and flora confined to the area.